Study on pressure-boosting stimulation technology in shale gas horizontal wells in the Fuling shale gas field. (1st September 2022) - Shi, Wenrui; Zhang, Chaomo; Jiang, Shu; Liao, Yong; Shi, Yuanhui; Feng, Aiguo; Young, Steven
Abstract: After more than seven years of commercial development in the Fuling shale gas field, most old wells in the main block are confronted with significant pressure decline, so shale gas production is lower than the critical fluid-carrying flow rate and considerably reduced production. Pressure-boosting stimulation technology can increase the pressure difference between flow pressure and transmission pressure, which improves gas transmission capacity, maintains production and subsequently improves the recovery. This study analyzes the pressure-boosting stimulation pattern and prediction method of the remaining recoverable reserves in the Fuling shale gas field. The findings show that the pressure-boosting stimulation pattern of a gas-gathering station can reduce the abandonment pressure of a gas well to the maximum extent and fulfill the requirements for the new adjustment wells in the gas-gathering station; therefore, it is a pressure-boosting pattern suitable for the Fuling shale gas field. Blasingame analysis method can effectively predict the production change of continuous recovery over the next ten years. In addition, the influence of water production in shale gas wells on pressure-boosting stimulation technology is discussed. The research results can provide experience and direction for the continuous improvement of gas recovery in the Fuling and the same type shale gas fields. Highlights: Gas-gathering station pressure-boosting pattern is suitable for the Fuling gas field. Blasingame method can effectively predict the recoverable reserves. Pressure-boosting stimulation effect will be affected by the water production.